2014
DOI: 10.1007/s40140-014-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective Ventilatory Approaches to One-Lung Ventilation: More than Reduction of Tidal Volume

Abstract: The thoracic surgical patient is at special risk for increased postoperative pulmonary complications, such as atelectasis, impaired lung function and pneumonia, as well as acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) with high mortality after lung resections. One-lung ventilation (OLV) induces proinflammatory responses especially in the ventilated lung, based on mechanical stress, persistent hyperperfusion, increased gas content and ventilation to perfusion mismatching. ALI may occur,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 112 publications
(116 reference statements)
0
9
0
4
Order By: Relevance
“…On the other hand, the Italian and Japanese anesthesiologists tend to recommend a low tidal volume (4 to 6 ml/kg PBW) for OLV [1,22]. Nevertheless, opinions from the expert anesthesiologists highlight that protective ventilation in thoracic anesthesia is not simply synonymous of a low tidal volume, but also involves the appropriate application of PEEP, alveolar recruitment and other ventilatory settings during OLV [23,24]. Most recently, a double-blind, [21].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Italian and Japanese anesthesiologists tend to recommend a low tidal volume (4 to 6 ml/kg PBW) for OLV [1,22]. Nevertheless, opinions from the expert anesthesiologists highlight that protective ventilation in thoracic anesthesia is not simply synonymous of a low tidal volume, but also involves the appropriate application of PEEP, alveolar recruitment and other ventilatory settings during OLV [23,24]. Most recently, a double-blind, [21].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Italian and Japanese anesthesiologists tend to recommend a low tidal volume (4 to 6 ml/kg PBW) for OLV [1,17]. Nevertheless, opinions from the expert anesthesiologists highlight that protective ventilation in thoracic anesthesia is not simply synonymous of a low tidal volume, but also involves the appropriate application of PEEP, alveolar recruitment and other ventilatory settings during OLV [18,19]. Most recently, a double-blind, randomized controlled trial conducted at the Samsung Medical Center (Seoul, Korea) demonstrated that driving pressure-guided ventilation (median ∆P of 9 cmH 2 O) during OLV significantly reduced the incidence of postoperative pulmonary complications compared with the conventional protective ventilation (tidal volume 6 ml/kg PBW, PEEP 5 cmH 2 O and recruitment) in thoracic surgery [20].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Italian and Japanese anesthesiologists tend to recommend a lower tidal volume (≤6 ml/kg PBW) for OLV [1,22]. Nevertheless, opinions from the expert anesthesiologists highlight that protective ventilation in thoracic anesthesia is not simply synonymous of a low tidal volume, but also involves the appropriate application of PEEP, alveolar recruitment and other ventilatory settings during OLV [23,24]. Most recently, a double-blind, randomized controlled trial conducted at the Samsung Medical Center (Seoul, Korea) demonstrated that driving pressure-guided ventilation (median ∆P of 9 cmH 2 O) during OLV signi cantly reduced the incidence of postoperative pulmonary complications compared with the conventional protective ventilation (tidal volume 6 ml/kg PBW, PEEP 5 cmH 2 O and recruitment) in thoracic surgery [25].…”
Section: Discussionmentioning
confidence: 99%